若直线y=kx+b与直线y=3x-1垂直,则( )
A: k=3
B: k=-3
C: [img=43x43]1803703bdedc15f.png[/img]
D: [img=59x43]1803703be6b8841.png[/img]
A: k=3
B: k=-3
C: [img=43x43]1803703bdedc15f.png[/img]
D: [img=59x43]1803703be6b8841.png[/img]
举一反三
- 若直线y=kx+b与直线y=3x-1垂直,则( ) A: k=3 B: k=-3 C: [img=43x43]1803669d78f9348.png[/img] D: [img=59x43]1803669d81e0769.png[/img]
- 若直线y=kx+b与直线y=3x-1垂直,则( ) A: k=3 B: k=-3 C: [img=43x43]18038de0440a756.png[/img] D: [img=59x43]18038de04cadba4.png[/img]
- 请将[img=111x25]17de91575ad9932.png[/img]写成程序表达的形式: A: y = (x - 1)(x + 3) B: y = (x - 1) * (x + 3) C: y = (x - 1) x (x + 3) D: y = (x - 1) . (x + 3)
- 设三阶方阵[img=117x75]17da6265af67565.png[/img]有特征值[img=36x21]17da6265c0f8ef3.png[/img],则[img=26x15]17da6265d451088.png[/img] ,[img=27x17]17da5b7f743dcc3.png[/img] . A: x=1, y=1 B: x=2, y=1 C: x=3, y=0 D: x=0, y=3
- 设y=kx+b,当x=1时,y=1:当x=2时,y=4,那么( ) A: k=3,b=-2 B: k=-2,b=3 C: k=-3,b=2 D: k=-3,b=-2